Repair bond strength of aged resin composite using different surface treatments and bonding protocols - Bandaru, Pydiahnaidu; Bolla, Nagesh; Garlapati, Rupadevi; Vemuri, Sayesh; Bandaru, Yamini (International Journal of Dental Materials, 2021)
Background: Repair of direct composites are less invasive than replacement, diminishing the risk of iatrogenic exposure of the pulp and the risk of detrimental to adjacent teeth, all in all, reducing the procession of the “restoration death spiral”.Aim: This study aimed to evaluate the repair bond strength of aged resin composites using different surface treatments and bonding protocols.Materials and Methods: A total of 45 discs (n=45) were fabricated of Nanohybrid composite measuring about 2.5 mm in height and 3.5 mm in diameter and were mounted in acrylic resin and subjected to 10,000 thermal cycles between 5-55 ? C with 30 seconds of dwell time in a thermocycler in order to simulate artificial ageing. All these samples were assigned into three groups (n=15) based on the surface treatment protocol. According to the bonding protocol, the samples in each group are further divided into three subgroups (n=5). After surface treatments of the aged composites, the application of bonding agent followed by new composite material was performed. All the samples were stored in distilled water at 37 ? C for 24 hours. The shear bond strength of the samples was measured using a universal testing machine at a crosshead speed of 1mm/min.Results: Among the groups, the mean bond strength in medium grain diamond bur and 37% phosphoric acid etchant with the universal bonding agent subgroup was higher 852.56±27.71 than the remaining groups. The lowest mean bond strength of 200.9±10.62 was observed in 37% Etchant with direct composite subgroup.Conclusion: Different combinations of surface treatments and bonding protocols affect shear bond strength differently. The highest shear bond strength values were achieved for the group where surface treatment was done with the combination of blue diamond bur and 37% phosphoric acid along with a universal bonding agent.